Consumers’ purchasing decision towards food products of small and medium enterprises - F., Diana-Rose; M. A., Zariyawati; K., Norazlina; M. N., Annuar; O., Manisah (Econjournals, 2016)
The gross domestic product (GDP) of Malaysia has continuously increased from year to year. All industry sectors are responsible for contributing to Malaysia’s GDP, including the food and beverage (F&B) industry. The sales within the Malaysian F&B retail industry were forecast to grow yearly. This study is to examine Malaysian consumers’ acceptance of F&B products of small and medium enterprises (SMEs). In depth, this study also tries to investigate whether consumers use experience when making a decision to buy SMEs’ F&B products in the hypermarket. Results from structural equation modeling shows that consumers are barely aware of the existence of SMEs’ F&B products and prefer to buy establish brands’ products in the hypermarket. Hence, we suggest SMEs be more prominent in marketing their products. This action will influence consumer decisions in choosing SMEs brands over established brands’ products.